Amygdala alterations during an emotional conflict task in women recovered from anorexia nervosa. (28th February 2016) - Bang, Lasse; Rø, Øyvind; Endestad, Tor
Abstract: The pathophysiology of anorexia nervosa (AN) is not completely understood, but research suggests that alterations in brain circuits related to cognitive control and emotion are central. The aim of this study was to explore neural responses to an emotional conflict task in women recovered from AN. Functional magnetic resonance imaging was used to measure neural responses to an emotional conflict task in 22 women recovered from AN and 21 age-matched healthy controls. The task involved categorizing affective faces while ignoring affective words. Face and word stimuli were either congruent (non-conflict) or incongruent (conflict). Brain responses to emotional conflict did not differ between groups. However, in response to emotional non-conflict, women recovered from AN relative to healthy controls showed significantly less activation in the bilateral amygdala. Specifically, while emotional non-conflict evoked significant activations of the amygdala in healthy controls, recovered AN women did not show such activations. Similar significant group differences were also observed in the hippocampus and basal ganglia. These results suggest that women recovered from AN are characterized by alterations within emotion-related brain circuits. Recovered women's absence of amygdala and hippocampus activation during non-conflict trials possibly reflects an impaired ability to process emotional significant stimuli. Highlights: We recruited women recovered from anorexia nervosa (AN) and age-matched controls. Neural responses to an emotional conflict task were recorded using fMRI. Trials were either congruent (non-conflict) or incongruent (conflict). Neural responses to emotional conflict did not differ between groups. AN women showed significantly less activation in the amygdalae during non-conflict.